Field Trips: A Basic Gizmo for Learning and Experiencing of Cultural Arts: NIL - Olubunmi Michael Odewumi (IJER (Indonesian Journal of Educational Research), 2019)
Changing method and environment promotes active participation, interest and meaningful teaching. Field trips allow students to have direct experience and contact with learning objects outside the classroom. This study therefore examined the efficacy of field trip on undergraduate fine and applied arts students in Nigeria University. Quasi‐experimental of pre-test and post-test design was adopted. 60 students were selected. Creative Arts Museum Achievement Test (CAMAT) was employed as test instrument. The result indicated significant difference in the achievements of students. It was therefore recommended that arts lectures should expose students to field trip for personal discovery and learning of arts.